Pemgaruh Faktor Psikologi dan Karakteristik Individu terhadap Keputusan Konsumen Makan dan Minum Pada Lopee Coffee Samarinda - Kharimansyah Imansyah; Pamasang S Siburian; Saida Zainurossalamia ZA (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the effect of variables Psychological Factors and characteristics of individual consumers Decision Against Spot On Loppe Caffee Samarinda.The theoretical basis used by management marketing analysis tools Multiple Regression Liner with 51  samples. The conclusion of this study: The function of multiple linear regression calculation result is Y = 0.126 + 0.256 + 0.341 X1 + 0.683 X2 X3. Psychological variables regression coefficient value (X1) and individual characteristics (X2) is positive, meaning that if an increase in the quality of psychological variables (X1) and individual characteristics (X2) will lead to an increase in consumer decisions to eat and drink at Loppe Coffee. Psychological positive and significant impact on consumer decisions to eat and drink at Loppe Coffee, so the hypothesis is accepted The individual characteristics of positive and significant influence consumer decisions eat and drink at Loppe Coffee, so the hypothesis is acceptedKeywords: Psychological Factors, Individual Characteristics, - Consumer Decision